The Influence Of Experiential Marketing And Customer Satisfaction On PT Rak Indonesia's Customer Loyalty - Geo Ardhana Dinata; Liling Listyawati; Sri Lestari, Damajanti (Cita konsultindo, 2026)
This research is directed to explore how experiential marketing experience and customer satisfaction are intertwined in shaping PT RAK Indonesia's customer loyalty. In an increasingly competitive business landscape, consumers no longer judge products simply by function, but by a series of experiences they feel throughout the process of interacting with the company. The research approach used is quantitative with an explanatory research type. A total of 96 respondents who are active customers of PT RAK Indonesia were selected as research samples. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The results of the analysis show that experiential marketing has a real and significant boost to customer loyalty. On the other hand, customer satisfaction does not show a significant direct effect on loyalty. However, when experiential marketing and customer satisfaction were tested together, they were shown to have a significant impact on customer loyalty. A determination coefficient value of 0.955 indicates that most of the variation in customer loyalty can be explained by both variables. These findings confirm that customer experience is the dominant element in building loyalty at PT RAK Indonesia.